LAS EMOCIONES EN LOS LIBROS DE TEXTO DE LA NUEVA ESCUELA MEXICANA - Martínez Blancarte, Ana María (2025)
Currently, the Mexican Educational System (SEM) is experiencing relevant and necessary changes, one of the issues that has emerged with great force is related to the role that educational institutions play in emotional training, although it is not a new term, its Incorporation as an educational innovation in the education curriculum is recent and responds to different social needs.  The New Mexican School (NEM) has implemented actions to address this situation, among them is the development of plans and programs, as well as the creation of free textbooks (LTG), which contribute to the training of the student. Therefore, the objectives of this partial qualitative research report are: 1. to analyze the emotional contents in ​​mathematics in the primary and secondary level LTG and 2. To identify in the plans and programs of the Benemérita Escuela Nacional de Maestros (BENM) and the Escuela Normal Superior de México (ENSM) these aspects, through a qualitative documentary methodology. Among the findings, it is noted that primary and secondary LTG consider greater sections for teaching emotions than mathematics and that the BENM and ENSM programs deal with emotions in two curricular spaces. It is concluded that the efforts on the part of the SEM or the NEM have not been sufficient for the emotional approach, however it is a beginning that should be the watershed of many proposals for students.